Protestant modernity: Weber, secularization, and protestantism - Carroll, Anthony J. (Univ. of Scranton Press, 2007)
Historical and systematic aspects of modern secularisation -- Setting the scene -- Secularisation in Weber's sociology of religion -- Secularisation in Weber's Wirtschaft und gesellschaft (WUG) and Munich speeches -- The Protestant heritage of Weber's theory of secularisation